2018
DOI: 10.1017/ice.2018.188
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship for acute-care hospitals: An Asian perspective

Abstract: Inappropriate use of antibiotics is contributing to a serious antimicrobial resistance problem in Asian hospitals. Despite resource constraints in the region, all Asian hospitals should implement antimicrobial stewardship (AMS) programs to optimize antibiotic treatment, improve patient outcomes, and minimize antimicrobial resistance. This document describes a consensus statement from a panel of regional experts to help multidisciplinary AMS teams design programs that suit the needs and resources of their hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 82 publications
(180 reference statements)
1
37
0
1
Order By: Relevance
“…Increasing emergence of multidrugresistant pathogens is considered to be one of the most urgent threats to global health [35,36]. This is particularly true for Asia-Pacific countries where antibiotic overuse has been a major problem, with multidrug-resistant pathogens on the rise [31,37]. While several factors contribute to the problem of multidrug resistance including antibiotic usage in animals, self-medication of patients and poor hygiene standards, overuse of antibiotics in the in-hospital settings has been recognized as a main driver [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing emergence of multidrugresistant pathogens is considered to be one of the most urgent threats to global health [35,36]. This is particularly true for Asia-Pacific countries where antibiotic overuse has been a major problem, with multidrug-resistant pathogens on the rise [31,37]. While several factors contribute to the problem of multidrug resistance including antibiotic usage in animals, self-medication of patients and poor hygiene standards, overuse of antibiotics in the in-hospital settings has been recognized as a main driver [36].…”
Section: Discussionmentioning
confidence: 99%
“…Also, fixed budget for the lab in some hospitals limit broader PCT implementation as costs and savings occur in different departments. PCT testing often limited to -one to three tests per patient [5,6] Limitation for measurement by government Some countries restrict PCT reimbursement to certain indications and time points [31] Lack of high-quality (sensitive) POC technology For primary care and smaller emergency care institutions, POC devices may help to implement a PCT strategy Currently available POC tests often have insufficient technical performance and are not validated to be used for antibiotic stewardship [32] Educational support Educational material on PCT Many physicians have no formal education for the use of PCT and educational material is scarce [33] General ASP education and resources Lack of well-established infectious disease clinical training for hospital pharmacists, and the paucity of infectious disease specialists to oversee ASPs [34] Cultural differences Self-medication of patients with antibiotics In some countries, over-the-counter use of antibiotics may overrule physicians [26] Patient expectation for antibiotics Patients are demanding antibiotics for some conditions even if no bacterial infection is evident. Education of patients and relatives may be needed to make them understand the problems of antibiotic overuse have shown that for inpatient treatment in the ward and the ICU, measuring a baseline level within the first 24 h is helpful with repeated levels within 24-72 h depending on the clinical situation.…”
Section: Topic Comment Referencesmentioning
confidence: 99%
“…This may be because of the insu cient number of events and short observation period. Further, several studies showed a synergistic effect of hand-hygiene improvement combined with ASP on microbiological outcomes in the hospital [14,24]. Thus, we should promote the implementation of hospital-based ASP with hand-hygiene intervention as well as a local-regional ASP to improve microbiological outcomes, and continue further outcome evaluation.…”
Section: Discussionmentioning
confidence: 97%
“…First, it is noteworthy that our study demonstrates the positive effect of our ASP even in a resource-limited setting. There is limited information on in-hospital ASP in Asia, and resources and settings are diverse among each country and hospital [9,13,14]. In Japan, the resources were generally insu cient to meet the demands for implementing an ideal ASP [15], and therefore there is a necessity in developing ID-trained pharmacists and ID specialists [9].…”
Section: Discussionmentioning
confidence: 99%
“…Szakirodalmi összefoglalók sora bizonyítja (11,12,13), hogy az intézményi szinten megfelelő szakmaisággal kialakított, a humán és tárgyi feltételek biztosításával létrehozott antibiotikum stewardship programok hosszú távon hozzájárulhatnak ahhoz, hogy a világszerte elterjedt multirezisztens kórokozók terjedését megfékezzük, a kórokozók antibiotikumokkal szembeni rezisztenciájának körét szűkítsük, vagy legalábbis megállítsuk. Az is egyértelműen bizonyított, hogy egyes intézmények ezirányú elszigetelt törekvései becsülendőek, de átfogó nemzeti program hiányában csekély eredményességgel járnak.…”
Section: öSszefoglalásunclassified